Developing country-specific questions about end-of-life care for nursing home residents with advanced dementia using the nominal group technique with family caregivers. Issue 4 (April 2022) - Bavelaar, Laura; Nicula, Maria; Morris, Sophie; Kaasalainen, Sharon; Achterberg, Wilco P.; Loucka, Martin; Vlckova, Karolina; Thompson, Genevieve; Cornally, Nicola; Hartigan, Irene; Harding, Andrew; Preston, Nancy; et al.
Abstract: Objective: We aimed to develop question prompt lists (QPLs) for family caregivers of nursing home residents with advanced dementia in the context of a study involving Canada, the Czech Republic, Italy, the Netherlands, the United Kingdom and Ireland, and to explore cross-national differences. QPLs can encourage family caregivers to ask questions about their relative's end-of-life care. Methods: We used nominal group methods to create country-specific QPLs. Family caregivers read an information booklet about end-of-life care for people with dementia, and generated questions to ask healthcare professionals. They also selected questions from a shortlist. We analyzed and compared the QPLs using content analysis. Results: Four to 20 family caregivers per country were involved. QPLs ranged from 15 to 24 questions. A quarter (24%) of the questions appeared in more than one country's QPL. One question was included in all QPLs: " Can you tell me more about palliative care in dementia?" . Conclusion: Family caregivers have many questions about dementia palliative care, but the local context may influence which questions specifically. Local end-user input is thus important to customize QPLs. Practice implications: Prompts for family caregivers should attend to the unique information preferences among different countries. Further research is needed to evaluate the QPLs' use.